E – Booking Bus Pariwisata Berbasis Web - Henriani; Hastuty, Ade (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Tourist bus transportation still uses a conventional system, resulting in the process of creating rental documents being relatively long, so computer equipment is needed to make it easier to create document reports. The aim of this research is to create an E-Booking application for a tourism bus rental system throughout Ajatapparang. Using a qualitative method based on a literature study conducted for 3 months in 2024 based on the PHP programming language and a Web-based MYSQL database. The results of making the application went well based on trials from several respondents, and the booking information data was directly read by the tourist bus company.